Association between EBV serological patterns and lymphocytic profile of SjS patients support a virally triggered autoimmune epithelitis - Barcelos, F (2021)
Sjögren's syndrome (SjS) is characterized by lymphocytic infiltration of exocrine glands, i.e. autoimmune epithelitis. Lymphocytes are central in SjS pathogenesis, with B-cell hyperactivity mediated by T-cells. B-cells are main targets of Epstein-Barr virus (EBV) infection, a frequently-suggested trigger for SjS. We aimed to evaluate how the EBV infection modulates B and T-cell subsets in SjS, including as controls Rheumatoid arthritis patients (RA) and healthy participants (HC). SjS patients presented decreased CXCR5+T-cells, although IL21-secreting Tfh and Tfc cells were increased. Tfc were positively correlated with ESSDAI scores, suggesting their relevant role in SjS pathogenesis. As previously described, SjS patients showed expanded circulating naïve B-cell compartments. SjS patients had a higher incidence of EBV-EA-D-IgG+ antibodies, characteristic of recent EBV-infection/reactivation. SjS patients with past infection or recent infection/reactivation showed increased CXCR3+Th1 and CXCR3+Tfh1 cells compared to those without active infection. SjS patients with a recent infection/reactivation profile presented increased transitional B-cells compared to patients with past infection and increased plasmablasts, compared to those without infection. Our results suggest EBV-infection contributes to B and T-cell differentiation towards the effector phenotypes typical of SjS. Local lymphocyte activation at ectopic germinal centres, mediated by Tfh and Tfc, can be EBV-driven, perpetuating autoimmune epithelitis, which leads to gland destruction in SjS.